Saúde Mental na Atenção Primária: o apoio matricial e a clínica ampliada em tempos de covid-19 - Cunha, Isabela de Oliveira da (2023)
This article aimed to discuss matrix support in mental health in Primary Health Care (PHC) in the Covid-19 pandemic context. Therefore, a thematic content analysis of the portfolios produced during the Multiprofessional Residency in Family Health was carried out. After analyzing the materials, four thematic units of discussion were created: (1) mental health in PHC; (2) matrix support in mental health in PHC; (3) PHC in the COVID-19 pandemic and the impacts for matrix support; and (4) strategies for matrix support in PHC. In view of this, a discussion was held on the main challenges encountered for mental health in PHC, as well as some potential of PHC for the organization of care in a network and on a territorial basis. Furthermore, it was observed that the emergency nature adopted by PHC in the pandemic context had a significant impact on matrix support. Regarding the practice of matrix support in PHC, the processes of communication between the teams and permanent education in mental health were highlighted as important aspects for the construction of expanded and shared care. Matrix support becomes the basis for the production of quality mental health in PHC and when characterized as praxis, it proves to be potent to overcome existing challenges and possible health crises, such as the COVID-19 pandemic.